Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian dengan Minat Beli sebagai variabel Intervening - Yuanita Rizky Mamluati; Sutrisno Sutrisno; Bayu Kurniawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to measure the influence of product quality and price on purchasing decisions with purchase intention as an intervening variable. This research was prepared based on the influence of product quality and price on purchasing decisions and purchasing interest. This type of research is quantitative research, which uses a research instrument in the form of a questionnaire which has been prepared in several statements and measured using a 1-5 Likert scale. The population used in this research is port coffee consumers. The sample in this study amounted to 160 respondents. The sample was taken using a simple random sampling method, meaning that the respondents who became the research sample were respondents who were met by the researcher when conducting research without paying attention to certain characteristics. Research data was analyzed using Structural Equation Modeling (SEM) which was run via AMOS 24. Hypothesis test results showed that product quality had an influence on purchasing decisions, price variables had an influence on purchasing decisions, product quality variables had an influence on buying interest, and price variables had an influence on interest. purchase, purchasing decisions influence purchasing interest and product quality and purchasing decisions influence purchasing interest and price influences purchasing decisions and purchasing interest.